ANALISIS PENGARUH STRUKTUR KEPEMILIKAN TERHADAP MANAJEMEN LABA (STUDI KASUS PADA PERUSAHAAN PERTAMBANGAN DI BEI PERIODE 2008-2013) - Naila ‘Izzah; Agus Purwanto (Diponegoro Journal of Accounting, 2016)
The purpose of this study was to analyze the factors affecting the company in earnings management in a mining company listed on the Stock Exchange in 2008-2013. The population of this research is all financial data of listed companies on the Stock Exchange 2008-2013 period. Sampling method used in this research is purposive sampling method. The sample used in this study are mining sector companies listed on the Stock Exchange in 2008-2013. The data used are secondary data from BEI. The analysis technique used is multiple linear regression analysis. Based on this research, the independent variable institutional ownership, foreign ownership, and government has positive influence on earnings management while managerial ownership has no effect on earnings management. Based Adjusted R Square is seen that the magnitude of the coefficient of determination indicated by the value of Adjusted R Square is equal to 0.166, this means that institutional ownership, managerial ownership, foreign ownership, government ownership, independent board, firm size and leverage are able to explain earnings management by 16,6%.